Interpretation of in situ borehole ice strength measurement tests - Masterson, D. M. (Canadian Journal of Civil Engineering, 1996)
A hydraulic borehole jack for the testing of ice confined compressive strength and elastic modulus through the depth of a 150 mm hole at regular intervals is described. Interpretation of the pressure and deformation information obtained is accomplished using standard equilibrium and compatibility equations for plate bearing tests applied to the expansion of a cavity of crushed material surrounded by an elastic medium. The jack tests yield confined compressive strength and elastic modulus. These are basic, universally understood, engineering properties of a material useful in practice. The jack has been used successfully to determine the in situ strength and stiffness at any combination of depths required in a wide variety of conglomerate freshwater and sea ice. The results have been used to verify the strength and bearing capacity of ice platforms and roads and to help quantify global ice loads and local ice pressures on offshore structures. Key words: ice, ice testing, borehole testing, ice strength, ice roads, ice structures, field testing, field strength testing, in situ strength, in situ testing, ice in situ testing, ice platforms.